Competence and economy: International adult literacy assessments, knowledge capital and economic performance - Polónyi, István (Central European Journal of Educational Research, 2026)
After reviewing the measurement of adult literacy (IALS and PIAAC), the paper examines how its outcome – referred to as knowledge capital – differs from human capital. The paper also analyses the relationship between adult literacy and economic performance, briefly highlighting the debates surrounding this issue. In addition, the article examines the relationship between knowledge capital and economic development in Hungary. Finally, the study discusses adult education as a possible policy response. The analysis points to the relatively weak performance of Hungarian adult literacy competence in international comparison. This highlights the potential importance of adult education in improving competitiveness, employability, and democratic participation.